Effect of intrathecal midazolam on single dose morphine-bupivacaine co-mixture for spinal analgesia in labour - Onah, Damian U.; Aggo, Alfred T.; Ebirim, Longinus N. (International Journal of Research in Medical Sciences, 2022)
Background: When spinal analgesia is used for relief of labour pain, a major challenge has been how to extend its duration without increasing the associated adverse effects. The aim of this study was to evaluate the effect of intra-thecal midazolam on pain relief by low dose bupivacaine and morphine mixture administered intrathecally to women in labour. Methods: 160 labouring women, aged between 18 and 40 years gave consent and enrolled for this comparative study. The women were randomly allocated into two equal groups, MBM and BM. Group MBM received intrathecal 2.0 mg midazolam, 2.5 mg bupivacaine and 150 mcg morphine. Group BM received intra-thecal 2.5 mg bupivacaine and 150 mcg morphine. An epidural bolus dose of bupivacaine 10 mg plus fentanyl 25 mcg was given whenever rescue analgesia was needed. Foeto-maternal parameters, were assessed and recorded. Results: Duration of effective spinal analgesia was significantly longer in group MBM than in group BM, p=0.0001. More participants in group BM had epidural rescue analgesia compared to group MBM, p=0.001. More participants in group MBM had adequate spinal analgesia till delivery compared to group BM, p=0.001. All the participants in both groups were able to ambulate without support after 30 minutes following the injection of spinal drugs. Nausea and vomiting occurred less commonly in group MBM than in BM, p=0.006. Conclusions: Addition of midazolam to bupivacaine-morphine co-mixture significantly prolonged the duration of spinal analgesia without affecting ambulation or causing any considerable maternal or neonatal adverse effect.